Device-based measurement of physical activity and sedentary behaviour after critical illness: A scoping review - Darren Murphy; Annette Henderson; Judy M. Bradley; Bronwen Connolly; Jason J. Wilson; Brenda O’Neill (PLoS ONE, 2025)
Introduction Measuring and promoting physical activity could support rehabilitation and recovery after critical illness. In recent years, there has been an emergence of the use of devices to measure both physical activity and sedentary behaviour in this population. Understanding device selection and processes for data analysis could be helpful for future research and practice when used with this population. Aims The aim of this review was to explore the current use of device-based physical activity instruments to measure physical activity and sedentary behaviour during and following critical illness. Methods A scoping review was conducted which followed the Arksey and O’Malley (2005) framework. A comprehensive search of four electronic databases (Medline, ProQuest, Scopus and CINAHL) was conducted using pre-agreed search terms. Screening and data extraction was conducted by two independent reviewers. Data were analysed descriptively by summarising and describing results that linked to the review questions. Results Twenty-two studies were included; the majority were observational (n=12), with one randomised control trial. Studies covered the continuum from intensive care admission to 18 months post-hospital discharge. A total of 11 devices were used to assess physical activity and sedentary behaviour, and many different processing decisions were used for data analysis. Physical activity levels were low in the intensive care unit and remained low following discharge from intensive care. Conclusion The use of device-based measurement of physical activity and sedentary behaviour after critical illness is an emerging research area. While several devices are available, this review highlights the need for agreed and standardised protocol(s) to guide the processing and analysis of data. Investment is also needed to support the recovery of physical activity and the reduction of excessive sedentary behaviour following discharge from the hospital.